2011
DOI: 10.1002/ejlt.201100203
|View full text |Cite
|
Sign up to set email alerts
|

Squalene – biochemistry, molecular biology, process biotechnology, and applications

Abstract: Squalene is a natural triterpene and an important intermediate of sterol and hopanoid biosynthesis in various types of cell from bacteria to human. Synthesis and further conversion of squalene are key steps in the metabolism of sterols and related components. Here we summarize the recent knowledge of squalene biochemistry, its molecular properties, and its physiological effects. We compare squalene biosynthetic pathways in different cell types and describe biotechnological strategies to isolate this lipid. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(184 citation statements)
references
References 293 publications
(336 reference statements)
5
168
0
3
Order By: Relevance
“…cerevisiae can accommodate itself in industrial processes with remarkable ease; therefore, it is a preferred species among the squalene and ethanol producing strains, (Naziri E, 2011;Spanova M, 2011). Hydroxymethylglutaryl CoA (HMG1) reductase catalyzes the rate limiting step of the squalene biosynthesis pathway and its overexpression has been reported to enhance the production of squalene in S. cerevisiae (Farhi M, 2011;Donal KA, 1997;Paddon CJ, 2013).…”
Section: Overproduction Of Squalene Simultaneously Reduces the Producmentioning
confidence: 99%
“…cerevisiae can accommodate itself in industrial processes with remarkable ease; therefore, it is a preferred species among the squalene and ethanol producing strains, (Naziri E, 2011;Spanova M, 2011). Hydroxymethylglutaryl CoA (HMG1) reductase catalyzes the rate limiting step of the squalene biosynthesis pathway and its overexpression has been reported to enhance the production of squalene in S. cerevisiae (Farhi M, 2011;Donal KA, 1997;Paddon CJ, 2013).…”
Section: Overproduction Of Squalene Simultaneously Reduces the Producmentioning
confidence: 99%
“…Squalene synthetase (SgSQS, EC:2.5.1.21) catalyzes the conversion of two molecules of farnesyl diphosphate (FPP) to squalene and it has been suggested that this is one of the important regulatory enzymes in squalene synthesis [35]. Cucurbitadienol synthase (SgCS, EC:3.4.99.33), belongs to the family of oxidosqualene cyclases (OSCs), and is responsible for the cyclization of 2,3-oxidosqualene to generate cucurbitadienol.…”
Section: Introductionmentioning
confidence: 99%
“…Squalene (2) was reported to exhibit anti-tumor activities against colon cancer in rodents. 30 It also reduced colonic aberrant crypt foci (ACF) formation and crypt multiplicity in laboratory rats, indicating potential chemopreventive activities against colon carcinogenesis. 31 In a study evaluating the anti-proliferative effects of squalene and other compounds from palm oil against two human breast cancer cell lines, MDA-MB-231 and MCF-7, it was found that there was a suppression of nuclear factor kappa-light-chain-enhancer of activated B-cells (NF-κB) in breast cancer cells exposed briefly to tumor necrosis factor-alpha (TNF-α), 32,33 hence affecting the mechanisms of apoptosis and carcinogenesis.…”
Section: Results and Discusionmentioning
confidence: 99%